2014
DOI: 10.1038/cr.2014.145
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of SPOROCYTELESS/NOZZLE in controlling Arabidopsis ovule development

Abstract: Ovules are essential for plant reproduction and develop into seeds after fertilization. SPOROCYTELESS/NOZZLE (SPL/NZZ) has been known for more than 15 years as an essential factor for ovule development in Arabidopsis, but the biochemical nature of SPL function has remained unsolved. Here, we demonstrate that SPL functions as an adaptor-like transcriptional repressor. We show that SPL recruits TOPLESS/TOPLESS-RELATED (TPL/TPR) co-repressors to inhibit the CINCINNATA (CIN)-like TEOSINTE BRANCHED1/CYCLOIDEA/PCF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 55 publications
1
74
0
1
Order By: Relevance
“…In addition, TCP-interacting proteins seem to participate in the modification of protein levels (Li et al, 2012;Efroni et al, 2013;Tao et al, 2013;Li and Zachgo 2013;Ho and Weigel 2014;Wei et al, 2015). However, a view of the whole network intertwined by TCP genes remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TCP-interacting proteins seem to participate in the modification of protein levels (Li et al, 2012;Efroni et al, 2013;Tao et al, 2013;Li and Zachgo 2013;Ho and Weigel 2014;Wei et al, 2015). However, a view of the whole network intertwined by TCP genes remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Bars = 25 µm. (E) Coexpression of 35-EXB1-RFP and 35S-GFP-SPL in tobacco leaves indicated that EXB1 were colocalized with SPL, a known nuclear transcriptional repressor (Yang et al, 1999;Wei et al, 2015). Bar = 100 µm.…”
Section: Exb1-regulated Genes Controlling Shoot Branchingmentioning
confidence: 99%
“…In the 35S-EXB1-GFP transgenic plants, clear green fluorescence was observed in the nuclei of trichome cells, demonstrating that EXB1 may be a nuclear protein ( Figures 3A to 3D). To further confirm that EXB1 is located in the nucleus, we generated 35-EXB1-RFP and 35S-SPL-GFP in which the known nuclear protein SPOROCYTELESS (SPL) was fused to GFP (Yang et al, 1999;Wei et al, 2015). Coexpression of the two fusing proteins in tobacco (Nicotiana benthamiana) leaves showed that they were colocalized in the nuclei ( Figure 3E).…”
Section: Exb1 Encodes a Wrky Transcription Factor With Transactivatiomentioning
confidence: 99%
“…Transcriptional repressors containing ethylene-responsive element binding factor (ERF)-associated amphiphilic repression (EAR) motifs play essential roles in control of phytohormone signaling, stress responses, and other biological processes (Ohta et al, 2001;Hiratsu et al, 2002;Szemenyei et al, 2008;Pauwels et al, 2010;Causier et al, 2012;Wei et al, 2015). A central mechanism in signal transduction of several phytohormones is the E3 ligase-mediated degradation of transcriptional repressors.…”
Section: Discussionmentioning
confidence: 99%